Pertanggungjawaban Pidana Korporasi Di Bidang Perpajakan (Studi Kasus Putusan Mahkamah Agung Nomor : 2239 K/PID.SUS/2012) - Arief Dwiatmoko; Bambang Surojo (Darma Cendika Catholic University, 2015)
Tax collection system by using the self-assessment system has been used by the taxpayer